Chlorination induced damage and recovery in marine diatoms: Assay by SYTOX® Green staining. Issue 2 (30th November 2017) - Venkatnarayanan, Srinivas; Sriyutha Murthy, P.; Nancharaiah, Yarlagadda V.; Kirubagaran, Ramalingam; Venugopalan, Vayalam P.
Abstract: Phytoplankton entrained into cooling water systems of coastal power stations are subjected to acute chemical stress due to biocides (chlorine) used for biofouling control. They are subsequently released into the environment, where they may survive/recover or succumb. Experiments were conducted to evaluate the susceptibility of a centric ( Chaetoceros lorenzianus ) and pennate ( Navicula sp.) diatom to in-plant administered concentrations of chlorine (0.2–0.5 mg/L, TRO). Viability of cells exposed to chlorine was assessed by SYTOX® Green fluorimetry and was compared with other conventional end points like total cell counts, chlorophyll a content and cellular autofluorescence. Results showed a concentration-dependant reduction in viability, chlorophyll a and autofluorescence. C . lorenzianus cells were more susceptible to chlorine compared to Navicula sp. SYTOX® Green staining appears to be a sensitive method to assess chlorine-induced damages. The data show that in-use levels of chlorination can potentially impact entrained organisms; however, they can recover when returned to coastal waters. Highlights: Rapid and sensitive assessment of chlorination-induced damage in diatoms using SYTOX® Green staining The centric diatom C . lorenzianus was more susceptible to chlorination than the pennate diatom Navicula sp. Diatom species recovered from the damage caused by in-use levels of chlorination (0.2–0.5 mg/L, TRO) Navicula sp., but not C . lorenzianus, recovered from exposure to 1.0 mg/L hypochlorite for 20 min.